Improving Potassium Recommendations for Agricultural Crops 2020
DOI: 10.1007/978-3-030-59197-7_7
|View full text |Cite
|
Sign up to set email alerts
|

Considering Soil Potassium Pools with Dissimilar Plant Availability

Abstract: Soil potassium (K) has traditionally been portrayed as residing in four functional pools: solution K, exchangeable K, interlayer (sometimes referred to as “fixed” or “nonexchangeable”) K, and structural K in primary minerals. However, this four-pool model and associated terminology have created confusion in understanding the dynamics of K supply to plants and the fate of K returned to the soil in fertilizers, residues, or waste products. This chapter presents an alternative framework to depict soil K pools. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 89 publications
0
21
0
Order By: Relevance
“…Loam and clay soils in WA may contain large amounts of nonexchangeable K in the interlayer of clay minerals such as illite (Pal et al 2001), but the effect of illite on K supply to crops has not been demonstrated. There is evidence that feldspars, that are relatively prevalent in soils of WA, can contribute significant quantities of bioavailable K to plants, potentially from sand-sized fractions rather than clay-sized fractions (Bell et al 2021b). More research is warranted to investigate the role of non-exchangeable K and feldspar K in crop K supply and availability in order to better predict the rates of K rundown where negative K balances occur.…”
Section: Clay Mineralogy In Wa Soilsmentioning
confidence: 99%
“…Loam and clay soils in WA may contain large amounts of nonexchangeable K in the interlayer of clay minerals such as illite (Pal et al 2001), but the effect of illite on K supply to crops has not been demonstrated. There is evidence that feldspars, that are relatively prevalent in soils of WA, can contribute significant quantities of bioavailable K to plants, potentially from sand-sized fractions rather than clay-sized fractions (Bell et al 2021b). More research is warranted to investigate the role of non-exchangeable K and feldspar K in crop K supply and availability in order to better predict the rates of K rundown where negative K balances occur.…”
Section: Clay Mineralogy In Wa Soilsmentioning
confidence: 99%
“…The contribution of non-exchangeable K to crop nutrition increases as exchangeable K decreases and can be important especially for soils with high contents of 2:1 layered clay minerals (Barré et al 2008;Damar et al 2020). The availability of non-exchangeable K for crops is also influenced by the crystallographic properties of soil mineral particles (Bell et al 2021). To measure only exchangeable K, numerous extractants are used, e.g., ammonium acetate (K-AA), ammonium acetate EDTA (K-AAE) in Switzerland, BaCl 2 -triethanolamine, NH 4 Cl, or NaHCO 3 (NFX 31-108, ISO 13536) (Colwell 1965;Mc Lean and Watson 1985;FAL 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, considering the multitude of existing methods, there is still a lack of information on the correspondence of some of the methods, for example K-AAE or K-CO 2 . Bell et al (2021) highlighted the weaknesses of this model with four pools. For instance, crop availability of K in the interlayer of various clay mineral types cannot be estimated through only one chemical extraction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1, and cation exchange reactions. This gives rise to the concept of K 'pools' with differing stabilities and availability to plants within soils, thoroughly explored by Bell et al (2021), who recognise 6 different K pools. These are: (1) structural K in feldspars and feldspathoids,…”
mentioning
confidence: 99%